User's Guide for an Evaluation Follow-Up System. [Volume 2] - Harris, J. A.; Pickens Area Vocational-Technical School, Jasper, GA. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This guide is designed to assist users in collecting evaluation/follow-up data primarily from supervisors of former vocational-technical school students. The guidelines, presented in five parts, provide a step-by-step checklist for implementing the system and acquiring measurable/reliable data applicable to individual or overall school programs. Questionnaire data is expected to provide a basis or means for program evaluation, program comparison, instructor's self-evaluation, instructional improvement, and staff improvement. Following the introduction, part 2 reviews the participant selection process and includes guidelines for student exit interviews, sampling of students placed in related and unrelated fields, and selection of former students placed in the field. Part 3 discusses conducting on-site activities which involve making appointments with former students and their supervisors, developing travel plans, conducting on-site interviews, and following up mail-in responses. In part 4 instructions are provided for checking questionnaire responses, coding the questionnaire for keypunching, processing the data, and updating student records. The concluding part of the guide examines various administrative, supervisory, and instructor uses of the questionnaire. Appendixes contain (1) the validated evaluation/follow-up questionnaire (student, instructor, former student, and supervisor forms), and (2) a sample visual chart for presentation. (This guide is designed to be used in conjunction with the technical report, CE 019 570.) (CSS)
Sponsoring Agency: Appalachian Regional Commission, Washington, DC.
ERIC Note: Questionnaire may not reproduce well due to small type and colored paper; For a related document, see CE 019 570 CE 019 570.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Data Processing; Educational Needs; Employee Attitudes; Field Interviews; Followup Studies; Graduate Surveys; Guidelines; Guides; Instructional Improvement; Job Skills; Occupational Information; Participant Characteristics; Personnel Evaluation; Program Evaluation; Program Improvement; Questionnaires; Self Evaluation; Staff Development; Student Evaluation; Supervisors; Teacher Evaluation; Test Validity; Vocational Education; Vocational Followup; Guides, Non-Classroom.; Tests/Questionnaires.